Drug Therapies for Patients with IgA Nephropathy: A Network Meta-analysis of Randomized Clinical Trials - Sridharan, Kannan; Sivaramakrishnan, Gowri (Current Clinical Pharmacology, 2020)
Background: Several drugs are used for treating IgA nephropathy (IgAN). We carried out a network meta-analysis evaluating these drugs. Methods: Electronic databases were searched for appropriate randomized clinical trials carried out in patients with IgAN. The primary outcome was proteinuria remission rates and there were several other secondary outcome measures. The risk of bias was assessed. Mixed treatment comparison estimates were modelled from direct and indirect comparison estimates. Grading of the evidence for key comparisons was carried out. Results: Fifty-seven clinical trials were included in the systematic review and 51 in the metaanalysis. Polyunsaturated fatty acids, corticosteroids/angiotensin receptor blockers (ARB), ARB, angiotensin converting enzyme inhibitors (ACEI), ARB/ACEI, corticosteroids/ACEI and hypolipidemics/ ARB were observed with significantly higher rates of proteinuria remission than the standard of care. Several benefits were observed with other drugs on the secondary outcome measures. A very low grade was observed for the interventions. Conclusion: We observed a few interventions to perform better in the management of IgAN. The results of this study will aid in further evaluation of such drugs that may assist in saving the resources and time. However, the readers should interpret the findings with great caution as the results might change with the advent of future head-to-head clinical trials.
Keywords: Corticosteroids